Redox-active sodium 3, 4-dihydroxy anthraquinone-2-sulfonate anchored on reduced graphene oxide for high-performance Zn-ion hybrid capacitors. Issue 23 (27th May 2022) - Yang, Kai; Hu, Lei; Wang, Yi; Xia, Jianxing; Sun, Mengxuan; Zhang, Yunpeng; Gou, Chao; Jia, Chunyang
Abstract : A high-performance ARS anchored on reduced graphene oxide aerogel film cathode with fast transmission dynamics, pseudo-capacitance characteristics, high energy and power density, flexibility, and applicability. Abstract : The exploration of high-performance Zn-ion hybrid capacitors (ZIHCs) has attracted extensive attention recently. However, achieving high energy and power density has always been a great challenge for the development of ZIHCs. Herein, we construct ZIHCs with a preeminent combination of high energy and power density characteristics by introducing a pseudo-capacitance adsorption mechanism at the cathode side. Sodium 3, 4-dihydroxy anthraquinone-2-sulfonate (ARS) was anchored on a porous graphene aerogel film (PGAF-ARS) through strong π–π stacking. Comprehensive physical characterization and DFT calculation revealed that the self-assembled porous structure of PGAF-ARS provides abundant active sites for adsorption/desorption of Zn 2+, and this adsorption mechanism usually occurred at specific CO sites, which provides additional pseudo-capacitance storage. Simultaneously, the porous structure of the cathode also ensures rapid electron/ion transfer characteristics. Therefore, PGAF-ARS based ZIHCs have a high specific capacity of 230.4 mA h g −1 at 0.3 A g −1 and an excellent capacity retention rate of 92.6% after 10 000 cycles at 5 A g −1 . Moreover, ZIHCs achieve ultra-high energy density (184.9 W h kg −1 ) and maximum power density (20.6 kW kg −1 ). Furthermore, coin-type capacitors and flexible quasi-solid Zn-ion hybrid capacitors (F-ZIHCs) also show superior accessibility and practicality in electrochemistry. This work provides a strategy for fabricating high-performance thin films for future flexible electronic devices.